The explanatory of the green building index (GBI) rating system: An overview - Azmi, Muhammad Aqmarul Azri; Yusoff, Mohd Nazaruddin; Md Hanafiah, Faizal (2016)
Climate change and the impacts of global warming, have forced both governments and industry to make substantial changes to the way that they operate and function.Countries throughout the globe have adopted various approaches and strategies for addressing climate change and driving sustainable development. As a result, the Malaysian Green Building Index (GBI) rating system was created to provide the building industry a common and verifiable mechanism to benchmark green property development.The establishment of the Green Building Index (GBI) rating system will allow us to undertake development in a more environment-friendly way.